Role of Dexmedetomidine by Improving Sleep Quality and Pain Control in Covid-19 Patients - Khalid, Maliha; Feroze, Faheem; Qamar, Saad bin; Abbas, Naseem; Farooq, Saeed; Siddiqui, Aisha (Journal of Rawalpindi Medical College, 2023)
OBJECTIVE: To demonstrate the effective role of Dexmedetomidine as a sedative and analgesic agent in Covid-19 patients when used in conjunction with the established treatment of Acute Respiratory Distress Syndrome. INTRODUCTION: Covid-19 disease is a deadly contagious disease with milder symptoms to a more severe form with acute respiratory failure, septic shock leading to even death. Literature study shows High Flow Nasal Oxygen therapy and prolonged prone position sessions to be beneficial in the treatment of ARDS, however, to facilitate those sessions, a sedative and anxiolytic agent must be added in the treatment. Therefore, this study was conducted to document the beneficial role of dexmedetomidine as a sedative agent. METHODOLOGY: Retrospective observational study which included 150 PCR positive patients admitted in Covid ITC, from 1st February 2021 to 31st July 2021 residing in the premises of PAF Air Base, Mushaf, Sargodha. Data was analyzed using SPSS software. RESULTS: Out of 150 patients, 120 (80%) were treated with High Flow Nasal Oxygen (HFNO), Dexmedetomidine infusion (DEXME) and long periods of prone position (PP) sessions. Among these 120 patients, 88 (73.3%) were discharged while 32 (26.67%) patients died of which 7 (21.875%) died while being on HFNO therapy and 25 (78.125%) patients were intubated. DEXME infusion was found to have a positive outcome (P-value <0.005) in the treatment of moderate to severe ARDS. CONCLUSION: Our findings suggest that DEXME infusion is beneficial in moderate to severe ARDS caused by SARS-CoV2 when given along with HFNO therapy and prolonged PP sessions, thereby, avoiding intubation.